Peran Penerapan Sistem Informasi Manajemen Sumber Daya Manusia Terhadap Efektivitas Kinerja Karyawan Pada PT Anugerah Tangkas Transportindo Group - Dede Puspa; Cecep Edi Hidayat; Feri Yahyadi (Universitas Tangerang Raya, 2022)
The purpose of this research is to determine the effect of Human Resources Information Management System on Effectiveness of Employee Performance at PT. Aungerah Tangkas Transportindo Group. The research method used is quantitative research methods obtained from questionnaires distributedgives. the results of this study are the application of Human Resources Information Management System had no effect on Employee Performance this is evidenced by the t count value of 0,693 is less than the t table 2,037 (0,693<2,037) and the significant value is 0.493 is the greater than 0,05 (0,493>0,05), so reject Ho and accept Ha